PENGGUNAAN BAHASA SLANG WARIA DI KOTA BARABAI - Nani Marliani M. Rafiek Jumadi (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2019)
AbstractThe Use Transgender Slangs in Barabai City. This study aims to describe and explain theuse of transgender slangs in the city of Barabai as well as to the describe and explain thefrom of the word formations in the use of transgender slangs in the city of Barabai. Thisresearch uses descriptive qualitative research method with sociolinguistic approach. Thedata of this research is from the speeches of the transgender people, so the data source isthe transgender people. Data collection was done by observation technique, interviewtechnique, recording technique, and technique of renotetaking. The data then weretranscribed, classified, presented and concluded. The instrument of this research is a tablethat classifies data in accordance with the types of word forms, namely the forms of theword based and the word formations. The results of this study indicate that there are 201words of the transgender slangs used in 62 discourse fragments analyzed which arecreated from the transgender language itself or from the word formations which endingsconsist of 12 categories and the formations are from the English language. The meaningsof these words have various meanings depending on the conversations carried out bytransgender people, for example: one word has many meanings and it depends on thecontents of the conversations they have. From the 60 discourse conversations, there are270 uses of slang words in the form of affixation process,i.e. prefixes, infixes (insertion),suffixes or confixes (prefix and suffix) and reduplication process.Key words: slang, transvestite, wordAbstrakPenggunaan Bahasa Slang Waria di Kota Barabai. Penelitian ini bertujuan untukmendeskripsikan dan menjelaskan penggunaan kosakata bahasa slang waria di kotaBarabai serta mendeskripsikan dan menjelaskan wujud kata bentukan dalam penggunaanbahasa slang waria di kota Barabai. Penelitian ini menggunakan jenis penelitian metodedeskriptif kualitatif dengan pendekatan sosiolinguistik. Data penelitian ini adalah darituturan para waria dan sumber datanya dari para waria. Pengumpulan data dilakukandengan cara teknik observasi, teknik wawancara, teknik rekaman, dan teknik catat. Dataitu lalu mentranskripsikan, mengklasifikasi, menyajikan serta menyimpulkan. Instrumenpenelitian ini berupa tabel yang mengklasifikasikan data sesuai dengan jenis wujud kata,yaitu wujud kata dasar dan kata bentukan. Hasil Penelitian ini menunjukkan bahwapenggunaan kosakata bahasa slang yang digunakan dari 62 penggalan wacana yang telahdianalisis terdapat 201 kosakata yang tercipta dari bahasa waria itu sendiri maupun daritata bentukan kata yang berakhiran yang terdiri dari 12 kategori dan tata bentukan daribahasa Inggris. Makna dari kata-kata tersebut mempunyai berbagai arti tergantung dari16percakapan yang dilakukan para waria, misalnya dari satu kata mempunyai banyak artidan itu tergantung pada isi pembicaraan atau percakapan yang mereka lakukan. Dan dari60 percakapan wacana terdapat 270 penggunaan kosakata bahasa slang dalam wujudkata bentukan berupa proses afiksasi yaitu prefiks (awalan), infiks (sisipan), sufiks(akhiran) maupun konfiks (awalan dan akhiran) dan proses reduplikasi.Kata-kata kunci: slang, waria, kata